2005
DOI: 10.1016/j.ccr.2005.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of single cytokeratin-positive cells from bone marrow reveals early mutational events in breast cancer

Abstract: Chromosomal instability in human breast cancer is known to take place before mammary neoplasias display morphological signs of invasion. We describe here the unexpected finding of a tumor cell population with normal karyotypes isolated from bone marrow of breast cancer patients. By analyzing the same single cells for chromosomal aberrations, subchromosomal allelic losses, and gene amplifications, we confirmed their malignant origin and delineated the sequence of genomic events during breast cancer progression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
191
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(200 citation statements)
references
References 44 publications
(56 reference statements)
3
191
0
6
Order By: Relevance
“…It has been shown that the early disseminated tumor cells, the potential metastatic progenitors, are genetically significantly less aberrant than the matched primary tumors. 39,40 The above issue requires further analysis in a considerably larger cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the early disseminated tumor cells, the potential metastatic progenitors, are genetically significantly less aberrant than the matched primary tumors. 39,40 The above issue requires further analysis in a considerably larger cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, molecular analysis has provided enough evidence to assume that cytokeratin-positive DTCs are malignant cells. [38][39][40][41][42] Nevertheless, several investigators use >2 categories to describe immunostained cells, including apoptotic cells, probable hematopoietic cells, or probable tumor cells. 24,25,37 The clinical significance of such multiple categories is under investigation.…”
Section: Classification Of Immunocytochemically Positive Cellsmentioning
confidence: 99%
“…En cas d'extrusion, une migration métastatique très précoce de cellules tumorales est possible. Or on sait que des cellules métastatiques ayant les caractéris-tiques génomiques de cellules tumorales « préinvasives» ont été détectées dans la moelle osseuse de patientes atteintes de cancer du sein [8].…”
Section: Un éPithélium Très Vigilantunclassified